Pedagogical Importance of Ecological Education of Preschool Children: Pentingnya Pedagogis Pendidikan Ekologis Anak Prasekolah - Qodirova, N Z; Botirova, N A (Universitas Muhammadiyah Sidoarjo, 2022)
The pedagogical significance of ecological education of preschool children, the love of mother nature, its care issues such as cultivating a child's love for nature and living beings through ecological education and the formation of devotion to the motherland are widely covered.